Empowerment Strategy Masyarakat Desa Wisata Kebonagung Kecamatan Imogiri Kabupaten Bantul Yogyakarta - Suharto (Media Wisata, 2017)
Research related to community empowerment strategy is taking a case study in Kebonagung tourist village, Imogiri, Bantul Yogyakarta. The purpose of this research is to find the right form of empowerment strategy that aligned with the community. Qualitative research models through the instrument of observation, interviews, and documentation to collect data and facts that occurred in the community based on primary data and secondary data through the data triangulation process. Interviews were conducted by researchers with determining the key person as resources that is the administrator of tourist village and the community. The strategies proposed in this research include cooperation strategy, cultural defection strategy, and conflict strategy through objective structural approaches as well as objective non-structural approaches. The results showed that community involvement in the existence of tourist village from various economic and socio-cultural aspects have a positive impact even though not yet fully. The openness of employment and business opportunity occurred very positively on the participation of the community in the provision of accommodation facilities, but in the social and cultural aspects has not been maximized. Empowerment strategy recommended through this research in order to reach the economic and socio-cultural aspects of the maximum is more priority to the strategy of cooperation in accordance with the culture of rural communities